Parasitoid wasps (Hymenoptera: Chalcidoidea) reared from Sarcophaga (Liopygia) ruficornis (Fabricius, 1794) (Diptera: Sarcophagidae) in northern Brazil - Antonielson B. Silva; Fernando S. Carvalho-Filho; Marcelo T. Tavares; Daniell R. R. Fernandes (Revista Chilena de Entomología)
The family Sarcophagidae is cosmopolitan and plays a significant role in organic matter decomposition. Some species have medical, veterinary, and forensic importance, as they can cause myiasis and act as vectors of pathogenic agents. Little is known about the natural enemies regulating sarcophagid population. The aim of this paper is to reduce the gaps in understanding the involved groups and their ecological interactions, providing new occurrence records for Brazil and the state of Pará. Here, we document for the first time the parasitoid wasp Dirhinus anthracia Walker (Hymenoptera: Chalcididae) parasitizing pupae of Sarcophaga (Liopygia) ruficornis (Fabricius) (Diptera: Sarcophagidae) under natural conditions, representing the first record of this species and genus in the Amazon region and northern Brazil; the first record of the genus and species Exoristobia philippinensis Ashmead (Hymenoptera: Encyrtidae) for Brazil and the neotropical region, and the first record of Brachymeria podagrica (Fabricius) (Hymenoptera: Chalcididae) in the state of Pará, Brazil.